The immediate effects of serving on shoulder rotational range of motion in tennis players - Williams, K.; Hebron, C. (British Journal of Sports Medicine, 2021)
Background A decrease in dominant shoulder internal and total rotational range of motion (ROM) has been found in tennis players immediately after competitive play. This can become a risk factor for shoulder injuries if certain thresholds are reached. The adaptation is theorised to result from follow through of the serve, requiring the shoulder to decelerate through eccentric action of external rotators. This theory has not been confirmed by empirical research comparing serving to groundstrokes.